2007
DOI: 10.1002/chin.200720110
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 1,2,3,4‐Tetrahydrocarbazoles and Related Tricyclic Indoles.

Abstract: ChemInform is a weekly Abstracting Service, delivering concise information at a glance that was extracted from about 200 leading journals. To access a ChemInform Abstract, please click on HTML or PDF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Reaction of 2-methoxy-4-nitro-phenylhydrazine with cyclohexanone in the presence of acetic acid was MW irradiation at 100 W at the temperature 140 0 C give 6-nitro, 8-methoxy 1,2,3,4-tetrahydrocarbazole 35 (Scheme 11) [33]. The yield of the product (35) was found 80 %.…”
Section: Vera Barbieri and Maria Grazia Ferlin Reported Mw Assisted Synthesis Of Substituted 1234tetrahydrocarbazolesmentioning
confidence: 99%
See 1 more Smart Citation
“…Reaction of 2-methoxy-4-nitro-phenylhydrazine with cyclohexanone in the presence of acetic acid was MW irradiation at 100 W at the temperature 140 0 C give 6-nitro, 8-methoxy 1,2,3,4-tetrahydrocarbazole 35 (Scheme 11) [33]. The yield of the product (35) was found 80 %.…”
Section: Vera Barbieri and Maria Grazia Ferlin Reported Mw Assisted Synthesis Of Substituted 1234tetrahydrocarbazolesmentioning
confidence: 99%
“…Figure 13 Synthesis of substituted 1,2,3,4-tetrahydrocarbazole (38 a-i) 3.3. Synthesis of 1,2,3,4-tetrahydrocarbazoles from 2-(2-nitrophenyl)-2-cyclohexene-1-ones Tricia L. Scott et al and coworkers reported synthesis of 1,2,3,4-tetrahydrocarbazoles (1, 1a-1e) from reduction of 2-(2-nitrophenyl)-2-cyclohexene-1-ones (39 a-f) using palladium on carbon under 1 atm of hydrogen gas at ambient temperature[35] (Scheme 13). The yield of the reaction was found 62-94 %.…”
mentioning
confidence: 99%